Pengaruh Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan dengan Komitmen Organisasional sebagai Variabel Intervening pada PT. Antar Lintas Sumatera Padang-Medan - Revina Marlin; Marta Widian Sari; Mutia Seplinda (Journal of Management and Creative Business, 2024)
This research aims to examine the influence of job satisfaction and work motivation on employee performance through organizational commitment. The data collection method is through surveys and distributing questionnaires, with a sample of 58 respondents. The analytical method used is structural equation modeling using smartpls. The research of this study conclude that : (1) Job satisfaction does not have a positive and significant effect on organizational commitment at PT. ALS Padang-Medan. (2) Work motivation does not have a positive and significant effect on organizational commitment at PT. ALS Padang-Medan. (3) Job Satisfaction has a positive and significant effect on Employee Performance at PT. ALS Padang-Medan. (4) Work motivation has a positive and significant effect on the performance of PT employees. ALS Padang-Medan. (5) Organizational commitment does not have a positive and significant effect on employee performance at PT. ALS Padang-Medan. (6) Job satisfaction does not have a positive and significant effect on employee performance through organizational commitment at PT. ALS Padang-Medan. (7) Work motivation does not have a positive and significant effect on employee performance through organizational commitment at PT. ALS Padang-Medan.